Lycium barbarum Reduces Abdominal Fat and Improves Lipid Profile and Antioxidant Status in Patients with Metabolic Syndrome. (8th June 2017) - de Souza Zanchet, Mayara Zagonel; Nardi, Geisson Marcos; de Oliveira Souza Bratti, Letícia; Filippin-Monteiro, Fabíola Branco; Locatelli, Claudriana
Abstract : Natural antioxidants present in fruits have attracted considerable interest due to their presumed safety and potential nutritional value. Even though antioxidant activities of many fruits have been reported, the effects of phytochemicals of goji berry (GB) in patients with metabolic syndrome have not been investigated. In this study, we examined anthropometric and biochemical parameters in patients with metabolic syndrome after the consumption of GB. The patients were divided into two groups, control (C) and supplemented (S), and followed up for 45 days. Participants were individually instructed to carry out a healthy diet, but additionally, an inclusion of 14 g of the natural form of goji berry in the diet during 45 days for the S group was proposed. After 45 days of study, a significant reduction in transaminases as well as an improvement in lipid profile in the S group was observed. Likewise, a significant reduction in the waist circumference of the S group was observed when compared with that of the C group, and increased glutathione and catalase levels associated with a reduction of lipid peroxidation. These results suggest that this is an effective dietary supplement for the prevention of cardiovascular diseases in individuals with metabolic syndrome.